1237. New York State Outpatient Regional Antibiogram for Urinary Pathogens: Have We Reached a Post Antibiotic Era for the Treatment of UTIs?. (26th November 2018) - Rank, Elliot; Lodise, Thomas P; Avery, Lisa; Bankert, Eve; Dobson, Erica; Dumyati, Ghinwa; Hassett, Stephen; Keller, Marina; Lubowski, Theresa; Pearsall, Matthew; Carreno, Joseph
Abstract: Background: Outpatient prescribing for acute uncomplicated cystitis is a significant driver of antimicrobial use. Empiric therapy should be based on local susceptibility data. However, there is limited guidance on regional susceptibility trends in outpatient settings. This study describes the epidemiology and prevalence of antimicrobial resistance in uropathogens in New York State outpatient settings to help inform empiric treatment decisions. Methods: Retrospective analysis of positive urine cultures sent to Quest Diagnostics in 2016 from outpatient settings. Cultures that grew ≥10 5 CFU/mL were included from 17 NYS counties. Bacterial identification and antimicrobial sensitivities were determined on the Vitek-2 using CLSI M-100 S-25 breakpoints. Data were summarized as proportions and stratified by age (<17, 18–64, ≥65) and sex. Results: Over 78, 000 isolates were included (Table 1). The most prevalent isolates were Escherichia coli (65.2%), Enterococcus spp. (11.9%), and Klebsiella pneumoniae (9.9%). E. coli was highly susceptible to nitrofurantoin (NTF, 97.2%) and cefazolin (CFZ, 89.9%) and less susceptible to trimethoprim–sulfamethoxazole (TMP-SMX, 72.9%) and ciprofloxacin (CIP, 78.0%). Enterococcus spp. was highly susceptible to NTF (99.0%) and ampicillin (99.8%). K. pneumoniae was highly susceptible to TMP-SMX (90.0%) and CIP (95.2%) and markedly less susceptible to NTF (42.0%). E. coli was more prevalent in females (69.7% vs. 39.6%, P < 0.001). Enterococcus was more prevalent in males (39.6% vs. 10.1%, P < 0.001). The prevalence of K. pneumoniae was similar in men and women (9.6% vs. 10.1%, P = 0.08). Resistance was more prevalent in males (NTF: 6.3% vs. 4.2%; TMP-SMX: 26.3% vs. 22.7%; CIP: 35% vs. 17.3%) and for adults ≥65 (NTF: 6.2% vs. 3.6%; TMP-SMX: 25.1% vs. 22.1%; CIP: 30.0% vs. 14.0%) P < 0.001 for all comparisons. Conclusion: NTF appears to be the best empiric choice for outpatient treatment of acute uncomplicated cystitis in New York State. TMP-SMX and ciprofloxacin should be avoided empirically. These data also highlight the necessity to obtain uropathogen sensitivity data to confirm empiric therapy or make appropriate adjustments in the outpatient setting. Table 1. Summary of Antimicrobial Susceptibilities Disclosures: T. P. Lodise Jr., Motif BioSciences: Board Member, Consulting fee.